MENDETEKSI PENGGUNAAN NARKOBA MENGGUNAKAN METODE CERTAINT FACTOR - Muharam, Fajar (JTIK (Jurnal Teknik Informatika Kaputama), 2020)
Narcotics stands for Narcotics, Psychotropic and other addictive substances. The head of the National Narcotics Agency (BNN) commissioner Heru Winarto 2019 said the abuse of narcotics among adolescents increased by 24-28% of adolescents who used drugs. In the drug user is eager to improve themselves to a better way and away from drugs. This is what underlies the need for an expert system application to diagnose the stages of drug users. This is what underlies the need for an expert system application to diagnose the stages of drug users. The method of intervention used by the author to diagnose the stages of drug users is the Certainty Factor method that uses a level of certainty used by experts to describe the level of confidence of a problem by bringing up the presentation. In this expert system application is expected to have facilities that can help users to find out at what stage the user is using drugs so that they can prevent drug users from continuing to use excessive or continuous.